A supramolecular assembly based on an engineered hemoprotein exhibiting a thermal stimulus-driven conversion to a new distinct supramolecular structure. Issue 51 (12th June 2017) - Oohora, Koji; Onuma, Yoshitaka; Tanaka, Yuta; Onoda, Akira; Hayashi, Takashi
Abstract : An engineered hemoprotein monomer forms a stable fiber-type assembly and metastable micelle-type assembly induced by transient thermal stimulus. Abstract : Supramolecular assembly of an engineered hemoprotein with an externally-attached heme moiety via an azobenzene or stilbene linker demonstrates drastic structural transitions between two distinct forms: the thermodynamically stable fiber-type assembly and the kinetically trapped metastable micelle-type assembly induced by transient thermal stimulus.